Enzymatic synthesis of glucose monodecanoate in a hydrophobic deep eutectic solvent - Hollenbach, Rebecca; Ochsenreither, Katrin; Syldatk, Christoph (MDPI, 2020)
Environmentally friendly and biodegradable reaction media are an important part of a sustainable glycolipid production in the transition to green chemistry. Deep eutectic solvents (DESs) are an ecofriendly alternative to organic solvents. So far, only hydrophilic DESs were considered for enzymatic glycolipid synthesis. In this study, a hydrophobic DES consisting of (-)-menthol and decanoic acid is presented for the first time as an alternative to hydrophilic DES. The yields in the newly introduced hydrophobic DES are significantly higher than in hydrophilic DESs. Different reaction parameters were investigated to optimize the synthesis further. Twenty milligrams per milliliter iCalB and 0.5 M glucose resulted in the highest initial reaction velocity for the esterification reaction, while the highest initial reaction velocity was achieved with 1.5 M glucose in the transesterification reaction. The enzyme was proven to be reusable for at least five cycles without significant loss of activity.